1984
DOI: 10.1530/jrf.0.0710017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scrotal insulation on the ability of ram testes to produce testosterone in vitro

Abstract: Testosterone production in testis tissue taken from rams that had been scrotally insulated for 28 days and from control animals was compared in the presence and absence of pregnenolone and LH. The absolute content of testosterone, but not its concentration was reduced in scrotally insulated rams. Tissue from treated animals was able to synthesize testosterone from exogenous pregnenolone as effectively as tissue from control rams, whilst LH and pregnenolone together had little additive effect. The addition of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In our study, we observed a decrease in motility, vigor, and mass motility and an increase in the percentage of cells with major and minor defects up to the fifth experimental week. Similar results were observed when rams were submitted to heat stress for 14 or 28 days [ 38 , 39 ]. Also, in the present study, acrosome and plasma membrane damage were observed in the sperm from the ejaculate after induced heat stress.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, we observed a decrease in motility, vigor, and mass motility and an increase in the percentage of cells with major and minor defects up to the fifth experimental week. Similar results were observed when rams were submitted to heat stress for 14 or 28 days [ 38 , 39 ]. Also, in the present study, acrosome and plasma membrane damage were observed in the sperm from the ejaculate after induced heat stress.…”
Section: Discussionsupporting
confidence: 82%
“…There is no obvious change in LC number (Kerr and Sharpe, 1989b). Evidence from the bull (Schanbacher, 1979) and ram (Schanbacher, 1980;Byers, 1984;Byers and Glover, 1984) suggest that similar LC changes may occur in these species after induction of seminiferous tubule damage, but in the adult mouse there is a dramatically different response (MendisHandagama et al, 1990a,b;. Instead of hypertrophy, the LCs shrink by more than half in size and in their cytoplasmic organelle content (including mitochondria and SER).…”
Section: Lc Changes After Disruption Of Spermatogenesismentioning
confidence: 99%
“…These changes were accompanied by an increase in the volume fraction occupied by Leydig cells. Scrotal insulation does result in a considerable decrease in testis weight (Byers, 1984) and it is possible that the apparent increase in Leydig cell volume is due largely to tubule shrinkage and the consequent aggregation of interstitial tissue into a smaller volume, as suggested by Bascom (1923) and Moore (1924) after cryptorchidism. This aggregation effect will be less pronounced in the perfused tissue used in the present study as space left after shrinkage of the seminiferous epithelium is partly accounted for by the dilated lymphatics.…”
Section: Morphometrymentioning
confidence: 99%
“…The purpose ofthe present study was to examine the effects of heat-induced testicular damage on plasma concentrations of hormones to clarify some of the relationships between gonadal hormones and the pituitary gonadotrophins. The androgenic response of heat-damaged testes in vitro is described by Byers (1984).…”
Section: Introductionmentioning
confidence: 99%